Arterial partial pressure of oxygen and diffusion function as prognostic biomarkers for acute pulmonary embolism. (April 2022) - Ye, Wenjing; Chen, Xi; Li, Xiaoming; Guo, Xuejun; Gu, Wen
Abstract: Background: Risk stratification for acute pulmonary embolism (PE) ignores the roles of respiratory function and gas exchange. We aimed to identify the role of arterial partial pressure of oxygen (PO2 ) and diffusion function as prognostic biomarkers. Methods: We collected the data from hospitalised patients with acute PE. We used Spearman's correlation coefficient and Cox regression analysis to explore the clinical and prognostic values of PO2 and predicted percentage diffusing lung capacity for carbon monoxide (DLCO%pred) to predict the 30-day mortality. Results: We included 309 patients (mean age: 67.93 ± 13.31 years); 46.6% were men, and 12.62% were haemodynamically unstable. The 30-day all-cause mortality rates in the high-, intermediate high-, intermediate low-, and low-risk groups were 7.7%, 4.7%, 2.9%, and 0.0%, respectively (P < 0.05). PO2 (P = 0.012) and DLCO%pred (P = 0.036) were significantly different between the four risk groups. There were strong correlations between PO2, DLCO%pred, PO2 *DLCO%pred, and other markers (P < 0.05), especially troponin I, N-terminal pro-brain natriuretic peptide, and systolic pulmonary artery pressure. PO2 and PO2 *DLCO%pred were prognostic factors for death in haemodynamically stable patients (hazard ratio [HR] 0.618, 95% confidence interval [CI] 0.389–0.980, P = 0.041, and HR 0.501, 95% CI 0.26–0.96, P = 0.036, respectively). A lower PO2 (<8 kPa) was associated with a higher risk of mortality in all patients and in haemodynamically stable ones (HR 9.462, 95% CI 2.365–37.860, P = 0.001, and HR 6.597, 95% CI 1.102–39.495, P = 0.039, respectively). Conclusions: PO2, PO2 *DLCO%pred, and PO2  < 8 kPa were predictors of 30-day all-cause mortality in all patients and haemodynamically stable ones. Trial registration: ChiCTR2000030448. Highlights: Risk stratification for acute pulmonary embolism ignores respiratory function. PO2 and DLCO%pred correlated with indicators used for risk stratification. PO2, PO2 *DLCO%pred, and PO2 of <8 kPa were predictors of 30-day all-cause death.